Current Issues in Knowledge Management 2019
DOI: 10.5772/intechopen.86255
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Spillover Effects: Impact of Export Learning Effects on Companies’ Innovative Activities

Abstract: The global nature of knowledge production has blurred the boundaries between many scientific and technical fields. New, enhanced processes, technologies, products, services, and business models emerge leveraging integrated solutions with different roots. The existing spillover or flow of knowledge has influenced the creation of new cross-disciplinary areas of research into this phenomenon: knowledge economics and management. This chapter explores the impact of knowledge spillover effects on companies' innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Organizations use effective human resource practices producing the pool of knowledge spillover for the company. The process of knowledge spillover occurs through communication, informal frequent interactions, direct and indirect ties, interactive culture, mutual consensus, guidance, commitment, team work, brainstorming and dialectical ways of interaction within the organization (Trachuk & Linder, 2019). The invariant role of human resource practices is grounded in the five defined levels of dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Organizations use effective human resource practices producing the pool of knowledge spillover for the company. The process of knowledge spillover occurs through communication, informal frequent interactions, direct and indirect ties, interactive culture, mutual consensus, guidance, commitment, team work, brainstorming and dialectical ways of interaction within the organization (Trachuk & Linder, 2019). The invariant role of human resource practices is grounded in the five defined levels of dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, with the increase in market competition, product homogeneity gradually increases. Most industry products and technology have externalities; therefore, the knowledge spillover effects of industry products and technology are significant [77]. Enterprises can cooperate in innovations; however, this type of innovation does not involve a simple technology product restructuring or secondary innovation.…”
Section: Mechanism Processmentioning
confidence: 99%
“…Empirical work testing for positive spillovers in innovation and discovery, the types of public goods that we focus on, found that “R&D spillovers are both prevalent and important” (Baldwin & Von Hippel, 2011; Griliches, 1992). These positive spillovers have been shown to have important effects on firms, increasing productivity (Czarnitzki & Kraft, 2012; Nagle, 2014), providing strategic advantages (Harhoff, Henkel, & Von Hippel, 2003), and building innovation capabilities (Altman, Nagle, & Tushman, 2014; Golovko & Valentini, 2014; Govindarajan & Ramamurti, 2011; Trachuk & Linder, 2019). Thus, there is good reason to believe that algorithm development could have positive spillovers, providing a country‐specific advantages for firms of that country (Mauri and de Figueiredo, 2017).…”
Section: Theory and Hypothesesmentioning
confidence: 99%